PENGARUH LINGKUNGAN KERJA, DISIPIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA ASN BAPPEDA KABUPATEN SITUBONDO - Dian Bintari Supriyatini; Karnadi Karnadi; Yudha Praja (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
This study aims (1) to find out the influence of the work environment, work disipin, and work motivation partially affect the performance variables of asn of the Situbondo District Development Planning Agency (2) to find out the influence of the work environment, work leadership, and work motivation to simultaneously affect the performance variables of the Asn of the Situbondo District Regional Development Planning Agency. (3) to know between the work environment, work leadership, and work motivation that most dominantly affect the performance of the ASN of the Situbondo District Development Planning Agency. The method used is qualitative. The result of the study is a multiple linear regression equation Y = 0.025 + 0.359X1 + 0.296X2 + 0.323X3 + e. Partially the work environment, work disipin, and work motivation have a significant effect with the performance of the Asn Regional Development Planning Agency of Situbondo Regency. The value obtained for the work environment variable is greater than the ttabel (2,408) > (2,026) and the sig value α 0.021 < 0.05, the value of the work discipline variable obtained is a thitung value greater than the ttabel (2,500) > (2,026) or sig α 0.017 < 0.05 and the value of the work motivation variable obtained is a thitung value greater than ttabel (2,258) > (2,026) or sig α 0.030 < 0.05. Simultaneously the work environment, work disipin, and work motivation have no significant effect on the performance of the ASN of the Situbondo District Development Planning Agency with a value of F calculates greater than F table or F calculates 57,560 > F table 2.86. Predominantly, the work discipline variables have the most dominant effect on ASN performance, with the value obtained at 2,500.